Variasi Radial Sifat Mekanika Kayu Malapoga (Toona ciliata M. Roem) Yang Berasal Sulawesi Tengah - Hapid, Abdul (Universitas Tadulako, 2019)
This research had the objectives to find out the variation mechanical properties of malapoga wood in the radial direction. Materials used in this research were a tree malapoga from Tojo Una-Una District and a tree from Sigi District Central Sulawesi. This study applied factorial experiment in completely randomized design. Factors of this research were site and radial direction. Testing of physical-mechanical properties of wood is done by using the method of British Standard Number 373 in 1957. The results showed that the physical-mechanical properties of malapoga wood the radial direction from the pith increased toward the bark. Air-dry moisture content was 15.57%. Specific gravity was 0.46. Static bending strength till proportional limit, MOE and MOR consecutively 446.77 kg/cm2, 59,69(103 kg/cm2), 595,81 kg/cm2.Keywords: Malapoga Wood, Mechanical Properties, Radial Direction